2012
DOI: 10.1155/2012/352028
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Subdural Hematoma Following Spinal Anesthesia: Report of Two Cases

Abstract: Postdural puncture headache and cerebral subdural hematoma are among complications of spinal anesthesia with some common characteristics; however misdiagnosis of these two could result in a catastrophic outcome or prevent unwanted results by urgent interventions. With the purpose of increasing awareness of such complications and a speedy diagnosis, we report two cases of postspinal anesthesia headache that was timely diagnosed as cerebral subdural hematoma and prevented the likelihood of a disastrous outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Chronic subdural hematomas after puncture of the spinal dura have been previously reported following spinal anesthesia. Moradi et al 7) reported that intracranial hypotension from CSF leakage after dural puncture can lead to a caudal shift of the brain, with subsequent traction on the arachnoid membrane and dural veins. This damages the blood vessels, which could result in blood leakage and the formation of a subdural hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic subdural hematomas after puncture of the spinal dura have been previously reported following spinal anesthesia. Moradi et al 7) reported that intracranial hypotension from CSF leakage after dural puncture can lead to a caudal shift of the brain, with subsequent traction on the arachnoid membrane and dural veins. This damages the blood vessels, which could result in blood leakage and the formation of a subdural hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations ranging from alterations in headache from postural to non-postural, vomiting, diplopia, cognitive changes, changes in consciousness level, focal neurological signs like ptosis, paresis, weakness, and language deficits are also noted. 2,4,5 The period of headache triggered by subdural hematoma is categorized into three patterns. The first pattern, which is the most common, is a headache that presents early (within four days) after dural puncture and lingers with subsequent onset of subdural hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…3 Due to unknown reasons, cerebral subdural hemorrhage after spinal anesthesia occurs more regularly on the left side, as early as six hours and at the latest by twenty-nine weeks. 5 Risk factors for the emergence of subdural collections are cerebral atrophy, cerebral aneurysms, blood dyscrasias, platelet anti-aggregation drugs, arteriovenous malformations, pregnancy, dehydration, alcohol consumption, multiple punctures, thick bore needles, epidural needles, and fenestrations from previous punctures. 5,6,7 Spinal anesthesia performed with fine needles of the Whitacre-, Sprotte-and Atraucan-type bevel have not been reported to prevent this complication.…”
Section: Discussionmentioning
confidence: 99%
“…The primary pathophysiology of this complication is unknown; however, there are some data that it is the same as PLPH, with some minor differences. Intracranial hypotension allows a caudal shift of the brain, with traction on the arachnoid mater and dural veins; this leads to lesions of the blood vessels and could result in blood extravasations and formation of SDH [3,12].…”
Section: Criteria Of Post-lumbar Puncture Headache According To Ichd-3mentioning
confidence: 99%